THE INFLUENCE OF WORK AND STUDY CONFLICTS, TIME MANAGEMENT AND QUALITY OF GUIDANCE SERVICES ON STUDENT COMPLETION OF STUDIES: Pengaruh Konflik Pekerjaan dan Studi, Manajemen Waktu dan Kualitas Layanan Bimbingan terhadap Penyelesaian Studi Mahasiswa Magister Manajemen Universitas Tadulako Palu - Simanjuntak, Lia Margaretha; Kaseng, Saharuddin; Rossanti, Niluh Putu Evvy (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This study aims to determine and analyze: the effect of work and study conflicts, time management and the quality of guidance services on the completion of the study of master of management students at Tadulako University Palu. The study population was 114 students of master of management at Tadulako University Palu. Due to the limited number of popu lation, to ensure the accuracy of the data in this study, researchers will use the entire population above as a research sample. The type of data in this study consists of quantitative data and qualitative data with data sources consisting of primary data and secondary data. While data collection techniques consist of interviews, questionnaires and observations with data analysis techniques using Structural Equation Model (SEM) Partial Least Square (PLS) analysis. The results showed that work and study conflict had no significant effect on study completion with a P value of 0.131>0.05. Time management has a significant effect on study completion with a P value of 0.000 <0.05. The quality of guidance services has a significant effect on study completion with a P value of 0.023 <0.05